Sugar Consumption, Dental Health and Foodways in Late Medieval Iin Hamina and Early Modern Oulu, Northern Finland. Issue 1 (1st January 2016) - Vilkama, Rosa; Kylli, Ritva; Salmi, Anna-Kaisa
Abstract : This article examines the modernization of northern Finnish food culture, especially in 17th- and 18th-century urban Oulu, by applying the methods of archaeology and history research. During the 17th century, the food culture was still quite conservative. Coffee, sugar, wheat flour, and fruit began entering the diet of affluent northern Finnish people from the 18th century onwards. The food culture of Oulu inhabitants is studied by comparing dental material retrieved from Oulu Cathedral graveyard to data obtained from historical document sources. A comparison point to the early modern bone material of Oulu is provided by late Middle Ages material from Ii, which lies north of Oulu on the coast of the Gulf of Bothnia. Carbohydrate consumption is related to many dental conditions, such as caries and calculus, which can be traced in archaeological human skeletal remains. The diets of males and females, as well as the diets of adults and children, are compared, in order to retrieve information on the emerging consumption of sugar in different groups, such as gender and age groups. The relationship between carbohydrate consumption and class identity in northern Finland is discussed.